Computation of Zagreb Polynomial and Indices for Silicate Network and Silicate Chain Network - Muhammad Usman Ghani; Mustafa Inc; Faisal Sultan; Murat Cancan; Alphonse Houwe (Journal of Mathematics)
The connection of Zagreb polynomials and Zagreb indices to chemical graph theory is a bifurcation of mathematical chemistry, which has had a crucial influence on the development of chemical sciences. Nowadays, the study of topological indices has become a vast effective research area in chemical graph theory. In this article, we add up eight different Zagreb polynomials for the Silicate Network and Silicate Chain Network. From these Zagreb polynomials, we catch up on degree-based Zagreb indices. We also provide a graphical representation of the outcome that describes the dependence of topological indices on the given parameters of polynomial structure.